2021
DOI: 10.3390/vaccines9060672
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 mRNA SARS-CoV-2 Vaccine Elicits High Avidity and Neutralizing Antibodies in Healthcare Workers

Abstract: The BNT162b2 vaccine, containing lipid nanoparticles-formulated mRNA encoding the full-length spike protein of SARS-CoV-2, has been employed to immunize health care workers in Italy, administered in two doses 21 days apart. In this study, we characterized the antibody response induced by the BNT162b2 vaccine in a group of health care workers, tested at baseline, after the first dose and after the booster. Thirty-nine subjects without previous exposure to SARS-CoV-2 were vaccinated with the BNT162b2 vaccine. Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
5
33
0
Order By: Relevance
“…Increased anti-S-RBD IgG antibody titers indicate seroconversion after either disease exposure or immunization ( 24 ). Robust SARS-CoV-2 IgG and neutralizing antibody levels in our study cohort after two doses of BNT162b2 mRNA vaccine suggest proficient antigen processing and presentation in all individuals as indicated by other BNT162b2 vaccination studies in diverse cohorts ( 15 , 25 27 ).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Increased anti-S-RBD IgG antibody titers indicate seroconversion after either disease exposure or immunization ( 24 ). Robust SARS-CoV-2 IgG and neutralizing antibody levels in our study cohort after two doses of BNT162b2 mRNA vaccine suggest proficient antigen processing and presentation in all individuals as indicated by other BNT162b2 vaccination studies in diverse cohorts ( 15 , 25 27 ).…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, sVNT was used and high levels of neutralizing antibodies were detected, indicating that BNT162b2 mRNA vaccine induced protective immunity in these individuals. In line with this, Pratesi et al showed that BNT162b2 mRNA vaccine induced increased levels of highavidity, anti-RBD IgG/IgA, and protective neutralizing antibodies in the vaccinated cohort (15). We further assessed whether presence of T2DM impacted the humoral immune response proficiency in response to BNT162b2 mRNA vaccine.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Failure of affinity maturation has been previously associated with vaccine failure [28] and some Authors have advocated that the development of high affinity antibodies targeting multiple epitopes of RBD are needed for effective long-term protection against SARS-CoV-2 [29] , [30] , [31] , [32] . Available studies [30] , [33] , [34] have shown parallel increases in avidity values, neutralizing activity and quantitative anti-RBD antibody titres up to 8 weeks from the second dose of vaccine but these short-term analyses were not designed to prove whether quantitative RBD-antibody level would predict neutralizing bioactivity and clinical protection on the long-term, when divergent kinetics of immunogenicity markers may unmask functional mechanistic associations [16] , [22] .…”
Section: Introductionmentioning
confidence: 99%